EFFECTS OF COVID-19 ANXIETY AND COVID-19 QUALITY OF LIFE ON COVID-19 BURNOUT IN PSYCHIATRIC NURSES - İbrahim GÜN (Rojan GÜMÜŞ, 2024)
Nurses are key professionals in fighting the COVID-19 pandemic and they provide services beyond expectations. Although psychiatric nurses are suffering from anxiety and burnout they need to enhance and protect their quality of life. The major aim of the study was to investigate the effects of COVID-19 anxiety on COVID-19 quality of life and COVID-19 burnout, and the impact of COVID-19 quality of life on COVID-19 burnout on psychiatric nurses. The descriptive-relational design was used. The sample consisted of 159 nurses working in a state psychiatric hospital in İstanbul, determined by convenience sampling method. The data of the study was collected by using the socio-demographic form, COVID-19 Anxiety Scale, COVID-19 Life Quality Scale, and COVID-19 Burnout Scale. Statistically significant relationships were found between COVID-19 anxiety, COVID-19 life quality, and COVID-19 burnout. The increase in the anxiety of psychiatric nurses due to COVID-19 also increases the negative effect on their quality of life. COVID-19 anxiety positively affects burnout related to COVID-19. The increase in the negative effects of COVID-19 on the life quality of nurses causes an increase in burnout levels. The effect of COVID-19 on their life quality and the burnout based on COVID-19 was investigated in the research. Nurses are surpassing traditional boundaries, providing their services without constraints to confront the challenges posed by the COVID-19 pandemic. Their dedication knows no bounds as they work tirelessly to navigate through these difficult times, transcending conventional limits to offer essential care and support. Policymakers can alleviate the increasing physical and psychosocial burden of psychiatric nurses by providing financial and moral support. Additionally, medical, psychosocial, and legal resources should be provided to psychiatric nurses.